Risk of Occupational Accidents in Workers with Obstructive Sleep Apnea: Systematic Review and Meta-analysis - Garbarino, Sergio (Sleep, 2016)
STUDY OBJECTIVES: Obstructive sleep apnea (OSA) is the single most important preventable medical cause of excessive daytime sleepiness (EDS) and driving accidents. OSA may also adversely affect work performance through a decrease in productivity, and an increase in the injury rate. Nevertheless, no systematic review and meta-analysis of the relationship between OSA and work accidents has been performed thus far. METHODS: PubMed, PsycInfo, Scopus, Web of Science, and Cochrane Library were searched. Out of an initial list of 1,099 papers, 10 studies (12,553 participants) were eligible for our review, and 7 of them were included in the meta-analysis. The overall effects were measured by odds ratios (OR) and 95% confidence intervals (CI). An assessment was made of the methodological quality of the studies. Moderator analysis and funnel plot analysis were used to explore the sources of between-study heterogeneity. RESULTS: Compared to controls, the odds of work accident was found to be nearly double in workers with OSA (OR = 2.18; 95% CI = 1.53–3.10). Occupational driving was associated with a higher effect size. CONCLUSIONS: OSA is an underdiagnosed nonoccupational disease that has a strong adverse effect on work accidents. The nearly twofold increased odds of work accidents in subjects with OSA calls for workplace screening in selected safety-sensitive occupations. COMMENTARY: A commentary on this article appears in this issue on page 1171. CITATION: Garbarino S, Guglielmi O, Sanna A, Mancardi GL, Magnavita N. Risk of occupational accidents in workers with obstructive sleep apnea: systematic review and meta-analysis. SLEEP 2016;39(6):1211–1218.